2020
DOI: 10.1098/rspb.2020.1189
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent modulation of natural approach behaviour in mice

Abstract: Specific features of visual objects innately draw approach responses in animals, and provide natural signals of potential reward. However, visual sampling behaviours and the detection of salient, rewarding stimuli are context and behavioural state-dependent and it remains unclear how visual perception and orienting responses change with specific expectations. To start to address this question, we employed a virtual stimulus orienting paradigm based on prey capture to quantify the conditional expression of visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…In addition, the Alpha-ON sustained RGCs in this particular retinal region differ from the same RGC-type in other regions of the retina as they have a significantly smaller dendritic tree radius and subtend a smaller area of physical space as well as have overlapping receptive fields ( Bleckert et al, 2014 ). Taken together, the cellular properties as well as the region in-front of the animal which provides their input are consistent with the requirements for tracking small and mobile targets ( Bleckert et al, 2014 ; Dean et al, 1989 ; Lettvin et al, 1959 ; Procacci et al, 2020 ). A recent study has shown that both wide-field and narrow-field neuronal types in the mouse superior colliculus play central roles in the detection and pursuit phases of this pursuit task, respectively ( Hoy et al, 2019 ), and consistent with this, Alpha-ON sustained RGCs having projections to the superior colliculus ( Martersteck et al, 2017 ).…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the Alpha-ON sustained RGCs in this particular retinal region differ from the same RGC-type in other regions of the retina as they have a significantly smaller dendritic tree radius and subtend a smaller area of physical space as well as have overlapping receptive fields ( Bleckert et al, 2014 ). Taken together, the cellular properties as well as the region in-front of the animal which provides their input are consistent with the requirements for tracking small and mobile targets ( Bleckert et al, 2014 ; Dean et al, 1989 ; Lettvin et al, 1959 ; Procacci et al, 2020 ). A recent study has shown that both wide-field and narrow-field neuronal types in the mouse superior colliculus play central roles in the detection and pursuit phases of this pursuit task, respectively ( Hoy et al, 2019 ), and consistent with this, Alpha-ON sustained RGCs having projections to the superior colliculus ( Martersteck et al, 2017 ).…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the Alpha-ON sustained RGCs in this particular retinal region differ from the same RGC-type in other regions of the retina as they have a significantly smaller dendritic tree radius and subtend a smaller area of physical space as well as have overlapping receptive fields (Bleckert, Schwartz et al 2014). Taken together, the cellular properties as well as the region in-front of the animal which provides their input are consistent with the requirements for tracking small and mobile targets (Lettvin, Maturana et al 1959, Dean, Redgrave et al 1989, Bleckert, Schwartz et al 2014, Procacci, Allen et al 2020. A recent study has shown that both wide-field and narrow-field neuronal types in the mouse superior colliculus play central roles in the detection and pursuit phases of this pursuit task respectively (Hoy, Bishop et al 2019), and consistent with this, Alpha-ON sustained RGCs having projections to the superior colliculus (Martersteck, Hirokawa et al 2017).…”
Section: Discussionsupporting
confidence: 56%
“…In this direction, we developed a novel automatic high-throughput training paradigm and demonstrated that mice can be trained to perform a two-alternative forced choice (2AFC) object classification task, which is typically used in primates to test object identification. While visually-guided operant behavioral tasks have been used previously in mice [7] [8] [9], here we show that mice can also learn to correctly discriminate objects under a 2AFC paradigm. Critically, this capability persisted even when they were presented with previously-unseen transformation of objects demonstrating that mice are capable of invariant object recognition.…”
Section: Introductionmentioning
confidence: 56%